Surface Controlled Electrochemical Sensing of Chlorpyrifos in Pinellia Ternate Based on a One Step Synthesis of Palladium-Reduced Graphene Nanocomposites. Issue 2 (1st January 2017) - Zhang, Yu; Xia, Zhi; Li, Qianzhu; Gui, Guofeng; Zhao, Gaoyu; Lin, Longli
Abstract : A novel acetylcholinesterase (AChE) biosensor for the detection of chlorpyrifos has been developed based on the immobilization of AChE on palladium-reduced graphene nanocomposites (rGO@Pd) modified glassy carbon electrode (GCE). The nanocomposites were synthesized by a one-step electrochemical co-deposition approach. Pd nanoparticles and rGO can be alternately attached onto the electrode surface, forming an interpenetrating network, which with excellent conductivity, catalysis, and biocompatibility offered an extremely hydrophilic surface for AChE adhesion. Under optimum conditions, the biosensor detects chlorpyrifos in two linear ranges, one is from 0.71 to 5.70 μM and the other is from 14.26 to 71.13 μM. The detection limit is 0.23 μM and the biosensor exhibits good performance such as reproducibility and stability, which makes it possible to provide a new and promising tool for the analysis of enzyme inhibitors.